1998
DOI: 10.1093/ije/27.3.431
|View full text |Cite
|
Sign up to set email alerts
|

Does childhood socioeconomic status influence adult health through behavioural factors?

Abstract: Childhood socioeconomic circumstances have an independent effect on adult health and health-related behaviour: the risk of health problems and health damaging behaviour is higher in lower childhood socioeconomic groups. The independent effect of childhood circumstances on adult health operates for a small part through unhealthy behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
120
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(124 citation statements)
references
References 22 publications
2
120
1
1
Order By: Relevance
“…The question of whether they represent separate in¯uences has rarely been addressed and if so, only in regard to BMI. 38,39 Interestingly, in this study, SES of origin, as ascertained by the occupation of the parent who had been breadwinner, was a strong predictor of general obesity, central adiposity and weight gain, even after controlling for the woman's own socioeconomic status and a number of other background characteristics. In addition, the interaction between parental and own occupation in relation to weight change demonstrates that social mobility signi®cantly affects the magnitude of weight change in this group of Swedish women, particularly among low socioeconomic classes.…”
Section: Weight Gain In Swedish Women Ph Lahmann Et Almentioning
confidence: 47%
See 1 more Smart Citation
“…The question of whether they represent separate in¯uences has rarely been addressed and if so, only in regard to BMI. 38,39 Interestingly, in this study, SES of origin, as ascertained by the occupation of the parent who had been breadwinner, was a strong predictor of general obesity, central adiposity and weight gain, even after controlling for the woman's own socioeconomic status and a number of other background characteristics. In addition, the interaction between parental and own occupation in relation to weight change demonstrates that social mobility signi®cantly affects the magnitude of weight change in this group of Swedish women, particularly among low socioeconomic classes.…”
Section: Weight Gain In Swedish Women Ph Lahmann Et Almentioning
confidence: 47%
“…Occupational variables related both to weight gain, current adiposity and fat patterning, with lower socioeconomic groups having higher values. Few previous studies of SES and obesity 36,37 or health 38 have found that early and late SES both have an independent predictive value for obesity. The question of whether they represent separate in¯uences has rarely been addressed and if so, only in regard to BMI.…”
Section: Weight Gain In Swedish Women Ph Lahmann Et Almentioning
confidence: 91%
“…Childhood SEP has not demonstrated a significant independent effect on smoking, alcohol consumption and leisure-time physical activity in adulthood in some studies (Greenlund et al, 1995;Blane et al, 1996). However, among GLOBE participants, a moderate-to-large independent effect of father's occupation on smoking status, alcohol consumption, body mass index (BMI) and physical activity was found, even after participants' own SEP was adjusted for (van de Mheen et al, 1998), and the direction of the independent effects were consistent with socioeconomic gradients in the behaviors (van de Mheen et al, 1998). The fact that childhood SEP demonstrated a significant independent effect only with intakes of some nutrients, and that the direction of these associations were variable may be due to the difficulty of estimating dietary intakes.…”
Section: Discussionmentioning
confidence: 98%
“…1,5,7,[21][22][23] The few studies that have attempted to determine how SES interacts with other sociogeographical factors associated with fitness have produced somewhat-contradictory findings. 1,5,7,13 The present results also agree with previous evidence 5 suggesting that SES-related differences in body size can explain at least partly the association between SES and physical fitness.…”
Section: Discussionmentioning
confidence: 99%